Exploiting tumour hypoxia and overcoming mutant p53 with tirapazamine. - Brown, J. M. (Nature Publishing Group, 1998)
Human solid tumours are composed of a significant proportion of hypoxic cells, i.e. cells with oxygen levels lower than those of normal tissues. Tumour hypoxic cells have been shown to have a negative impact on the response of solid tumours to radiation therapy and chemotherapy. However, these low cellular oxygen levels can be exploited by a drug that is specifically activated to a cytotoxic metabolite at these low levels. Tirapazamine is a novel bioreductive agent with selective cytotoxicity to hypoxic tumour cells, irrespective of their p53 status or apoptotic response, and acts synergistically with cisplatin. This potentiation is dependent on an interaction that can only take place in a hypoxic environment, resulting in a significant sensitization of the cells to cisplatin cell killing, with no increase in the systemic toxicity of cisplatin. Thus, the low cellular oxygen levels common in solid tumours can be turned from disadvantage to advantage using the hypoxia-selective cytotoxic drug tirapazamine.